Students’ Attitudes toward Drama Activities and Its Correlation to Their Narrative Reading Achievement - Astiara Larasati; Rita Hayati; Fiftinova Fiftinova (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: The objectives of this study were to fid out: (1) how the attitude toward drama activities of the seventh semester students of English Education Study Program of Sriwijaya University was,(2) the level of the students’ narrative reading achievement, (3) whether or not there was a signifiant correlation between students’ attitudes toward drama activities and their narrative reading achievement, and (4) whether or not there was a signifiant contribution of students’ attitudes toward drama activities to their narrative reading achievement. The population of this study was all of the seventh semester students of English Education Study Program of Sriwijaya University in academic year 2016/2017 with the total number of 93 students. Purposive sampling was applied and 45 students were chosen as the sample. The correlational research design was used in this study. The data were collected by using a questionnaire about attitudes toward drama activities and narrative reading test. Pearson product moment correlation coeffient of SPSS version 22 was used for analyzing the data. The results showed that (1) the students gave positive attitudes toward drama activities, (2) the level of students’ narrative reading achievement was categorized into good to average categories, (3) there was a weak signifiant correlation between students’ attitudes toward drama activities and the students’ narrative reading achievement (r= 0.333), and (4) it was also determined that there was 11.1% contribution of students’ attitudes toward drama activities to students’ narrative reading achievement.Keywords: attitude, drama activities, narrative reading achievementAbstrak: Tujuan penelitian ini adalah untuk mengidentifiasi: (1) bagaimana sikap mahasiswa semester tujuh Program Studi Pendidikan Bahasa Inggris Universitas Sriwijaya terhadap kegiatan drama, (2) tingkat prestasi mahasiswa dalam membaca naratif, (3) ada atau tidak ada hubungan signifian antara sikap siswa terhadap kegiatan drama dan prestasi membaca naratif mereka, dan (4) ada atau tidak ada kontribusi signifian sikap siswa terhadap kegiatan drama pada prestasi membaca naratif mereka. Populasi dari penelitian ini adalah seluruh mahasiswa semester tujuh Program Studi Pendidikan Bahasa Inggris Universitas Sriwijaya tahun ajaran 2016/2017 yang berjumlah 93 mahasiswa. Teknik purposive sampling diterapkan dan 45 siswa dipilih sebagai sampel penelitian. Desain penelitian korelasional digunakan dalam penelitian ini. Pengumpulan data dilakukan dengan menggunakan angket mengenai sikap siswa terhadap kegiatan drama dan tes membaca naratif. Koefiien korelasi Pearson Product Moment dari SPSS versi 22 digunakan untuk menganalisis data. Hasil penelitian menunjukkan bahwa: (1) siswa menunjukkan sikap positif terhadap kegiatan darama, (2) tingkat prestasi membaca naratif siswa berada dalam kategori baik hingga sedang, (3) terdapat hubungan signifian yang lemah antara sikap siswa terhadap kegiatan drama dan prestasi membaca naratif (r = 0,333), dan (4) juga terdapat 11,1% kontribusi sikap siswa terhadap kegiatan drama pada prestasi membaca naratif siswa.Kata-kata kunci: sikap, kegiatan drama, prestasi membaca naratif